2017
DOI: 10.21467/ajgr.3.1.20-33
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine-induced Changes in Blood Pressure and Heart Rate in Pre-hospital Intubated Patients

Abstract: A B S T R A C TWhen a patient experiences trauma, pre-hospital rapid sequence intubation (RSI) is often the course of action. While RSI is associated with favorable neurological outcomes among traumatic brain injury patients, it also carries the risk of increased hypotension and bradycardia. Ketamine is a fast-acting anesthetic agent used in RSI, attractive due to its ability to raise heart rate (HR) and blood pressure (BP) and thus potentially lessening the severity of RSIrelated hypotension and bradycardia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The transient isolated bradycardia (without other cardiovascular abnormalities) that was witnessed resolved spontaneously. Sheth et al have postulated that oldage, lower baseline vitals, and non-trauma patients are more likely to predict the occurrence of bradycardia after ketamine injection [6]. We believe that the old age and low baseline heart rate could have resulted into the bradycardia response.…”
Section: Discussionmentioning
confidence: 77%
“…The transient isolated bradycardia (without other cardiovascular abnormalities) that was witnessed resolved spontaneously. Sheth et al have postulated that oldage, lower baseline vitals, and non-trauma patients are more likely to predict the occurrence of bradycardia after ketamine injection [6]. We believe that the old age and low baseline heart rate could have resulted into the bradycardia response.…”
Section: Discussionmentioning
confidence: 77%
“…The effect of ketamine is ambiguous, although increasing the tension of the sympathetic nervous system causes an increase in HR, BP, and SV (Stroke Volume) while maintaining SVR. Still, in some patients, it may have a negative inotropic effect, causing hypotension and bradycardia [ 81 ]. Taking into account the effects mentioned above, hypotension when using OFA may be a problem and require the use of sympathomimetics such as ephedrine or catecholamines more frequently and in higher doses than in conventional anesthesia with multimodal analgesia, as well as more aggressive fluid therapy [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sheth et al . 2018[ 17 ] studied the effect of ketamine on HR and BP during Rapid Sequence Intubation (RSI) and found that higher doses (>200 mg) and moderately high doses (151–200 mg) of ketamine was more associated with hypertension than lower doses. Patients who received ketamine doses >150 mg were 1.3 times more likely to develop hypotension or hypertension after ketamine administration when compared to patients who received doses <150 mg; However, the results of this study are similar to the results of present study.…”
Section: Discussionmentioning
confidence: 99%